2022
DOI: 10.1097/sla.0000000000005390
|View full text |Cite
|
Sign up to set email alerts
|

Grading Pancreatic Neuroendocrine Tumors Via Endoscopic Ultrasound-guided Fine Needle Aspiration

Abstract: Objectives: To identify factors associated with concordance between World Health Organization (WHO) grade on cytological analysis (cgrade) and histopathological analysis (h-grade) of surgical specimen in patients with PanNETs and examine trends in utilization and accuracy of EUS-FNA in preoperatively predicting grade. Background: WHO grading system is prognostic in pancreatic neuroendo-crine tumors (PanNETs). The concordance between c-grade and h-grade is reported to be between 50% and 92%. Methods: A multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Thirdly, we identified tumor size, location, and grade as independent prognostic variables for the presence of LNM after resection (Table 4). Since tumor size, tumor location, and tumor grade can potentially be identified preoperatively [28][29][30], we used these parameters for LNM prediction and found the best performance in the combined prediction model (Table S1). For instance, a T1 G2 pNET situated in the pancreatic head was considered a high-risk situation given its association with lymph node metastasis (LNM) in 18% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, we identified tumor size, location, and grade as independent prognostic variables for the presence of LNM after resection (Table 4). Since tumor size, tumor location, and tumor grade can potentially be identified preoperatively [28][29][30], we used these parameters for LNM prediction and found the best performance in the combined prediction model (Table S1). For instance, a T1 G2 pNET situated in the pancreatic head was considered a high-risk situation given its association with lymph node metastasis (LNM) in 18% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts have been performed by others with the intent to assess the validity of pretreatment tumor grading of PanNETs by the use of samples acquired by EUS-guided sampling 41 . In a recent, retrospective publication, Leeds and colleagues concluded that EUS-FNB (n = 26) was superior to EUS-FNA (n = 35) in the diagnosis of PanNET.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, careful patient selection for lymph node-sparing resections can help reduce short-term and long-term postoperative morbidity without impairing long-term outcomes in selected patients. Reviewing preoperative imaging for suspicious lymph nodes and performing endoscopic ultrasound guided FNA can help to determine nodal status prior to an operation in patients with small PNETs 32. Lymph node-sparing procedures should be considered in patients without suspicious lymph nodes on imaging or high-risk features on endoscopic ultrasound guided FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing preoperative imaging for suspicious lymph nodes and performing endoscopic ultrasound guided FNA can help to determine nodal status prior to an operation in patients with small PNETs. 32 Lymph node-sparing procedures should be considered in patients without suspicious lymph nodes on imaging or high-risk features on endoscopic ultrasound guided FNA.…”
Section: Discussionmentioning
confidence: 99%